The Impact of Spin-off Policy on the Efficiency of Sharia Insurance in Indonesia using DEA approach - Abdul Ghoni; Erny Arianty (Journal of Islamic Economics Lariba, 2021)
This study aims to determine the impact of the spin-off on the level of efficiency of Sharia insurance in Indonesia by using the Data Envelopment Analysis (DEA) method. This study uses data from companies that have undergone a spin-off, namely Jasindo Syariah and Askrida Syariah, both before the spin-off and after the spin-off. Input data are assets, operating expenses, while output data are profit and operating income for a period of 5 years each. From the results of data processing, it shows that the two companies experienced a decrease in their level of efficiency towards profits after spin-off, but the level of efficiency on income, for Sharia Jasindo are relatively stable, while the Sharia Askrida has decreased.